Upaya Peningkatan Kemampuan Menemukan Isi Cerita dalam Buku di MIS Ibnu Sina Bogor: UPAYA PENINGKATAN KEMAMPUAN MENEMUKAN ISI CERITA DALAM BUKU DI MIS IBNU SINA BOGOR - Tita Hasanah; Ghaniyah Geulis Arifin; Muhamad Robie Awaludin S. (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2026)
This community service activity aims to improve students' ability to find story content through the use of interactive picture storybook media in science learning on social and cultural diversity in Indonesia at MIS Ibnu Sina Bogor. The activity was carried out on 28 fourth grade students using a participatory approach through the stages of needs analysis, activity planning, learning implementation, and activity evaluation. The media used was an interactive picture storybook designed to help students understand the story content through image visualization and interactive activities. Evaluation techniques were carried out through observation, documentation, and essay tests on the ability to find story content. The results of the activity showed that the use of interactive picture storybook media was able to increase student engagement in learning, increase reading interest, and help students understand the characters, plot, setting, and moral messages in the story. The evaluation results showed that the average post-test score of students reached 70.80, indicating that students' ability to find story content was in the good category. In addition, students appeared more active, enthusiastic, and confident during the learning process.